An Approach To Platform Design Using Design And Performance parameters Interactions. - Umar, Alias; Mohd Ripin, Zaidi; Abdullah, Ahmad Baharuddin (2005)
To respond to the challenge of agile manufacturing, companies are striving to provide a large variety of products at a low cost.